Are Greeks’ Unconcerned about Ethical Market Choices?" - DELISTAVROU, Antonia; TILIKIDOU, Irene (Journal of Economic Development, Environment and People, 2014)
An Ethical Unconcern (EthU) scale was constructed and its impact on Positive Ethical Consumption was examined. The procedure of EthU included literature search, brainstorming and discussion groups to generate the preliminary pool of 99 items, refinement of the scale via a students’ survey by the employment of item-to-total correlation and alpha-if-item deleted techniques. The initial scale was tested in a consumer survey conducted in the urban area of Thessaloniki, Greece. Item-to-total correlation and alpha-if-item deleted techniques were applied again, followed by Exploratory Factor Analysis (EFA) by the employment of PCA. The procedure left 21 items in five factors with eigenvalues greater than 1 explaining 61.34% of the variance. The five factors were named Boycott/ Discursive, Fair-Trade, Scepticism, Powerlessness and Ineffectiveness. The AMOS SPSS was then used to conduct confirmatory factor analysis. Goodness-of-fit results indicated that the measurement model fit the data well (χ2=594.226, p<0.000, CFI=0.926, NFI=0.899, TLI=0.910, RMSEA=0.066). The examination of the Positive Ethical Consumption indicated rare to occasional ethical buying choices among Greek consumers. The inhibiting role of Ethical Unconcern on Positive Ethical Consumption was found to be rather low.